Detection of Chlamydia trachomatis in male and female urine specimens by using the amplified Chlamydia trachomatis test. - Mouton, J W (1997)
The amplified Chlamydia trachomatis test (AMP-CT; Gen-Probe), a new diagnostic test for the detection of Chlamydia trachomatis, was evaluated with urine specimens from 1,000 patients visiting the outpatient department for sexually transmitted diseases at the University Hospital Rotterdam, Rotterdam, The Netherlands, by comparing the results to those of cell culture. From February 1996 to July 1996, urine samples for the AMP-CT test and urethral swabs for cell culture were collected from 544 men, while cervical swabs from 456 women were also taken for cell culture. Positive test results were obtained for 130 (13%) of the patients. AMP-CT test and cell culture results were discordant for 70 (7%) specimens. Analysis of the samples with discordant results was performed by an in-house PCR. After resolution of the discordant results, the sensitivity, specificity, and positive and negative predictive values of the AMP-CT test were 84.3, 98.8, 89.6, and 98%, respectively, for samples from females and 100, 99.2, 93.1, and 100%, respectively, for samples from males, while for cell culture these values were 72.5, 99.2, 92.5, and 98%, respectively, for samples from females and 57.4, 99.0, 86.1, and 95.4%, respectively, for samples from males. We conclude that the AMP-CT test is a fast and reliable test for the detection of C. trachomatis in urine specimens from females and, in particular, males.